Manfaat media digital dalam pengembangan promosi paket umrah di PT.AQM Tour and Travel Kota Bengkulu - oktaripramudita; Eka Sri Wahyuni; Idwal B (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
This study aims to find out how much benefit digital media has in promoting Umrah packages and what forms of digital media are used by PT. AQM Tour And Travel analysis used is to use qualitative methods. Data collection techniques are carried out by interview observation techniques or direct interviews with sources so that scientific answers, documentation, and literature studies are found. The data sources of this research are primary data and secondary data from research results showing PT. AQM Tour And Travel uses more and makes great use of digital media to promote Umrah packages, and worse for pilgrims it is easier to find information about Umrah and Umrah packages with digital media.